Differential bone marrow homing capacity of VLA-4 and CD38 high expressing chronic lymphocytic leukemia cells. - Gabriele Brachtl (Public Library of Science (PLoS), 2011)
Background VLA-4 and CD38 predict a poor clinical outcome in chronic lymphocytic leukemia (CLL). We used CLL samples with discordant VLA-4/CD38 risk to address their individual roles in human bone marrow infiltration (BM), CLL cell homing to murine BM, and in supportive CLL cell-stromal cell interactions. Methods VLA-4, CD38, and Ki-67 expression was measured in CLL cells from peripheral blood (PB) and bone marrow (BM) aspirates. CLL BM infiltration rates, routinely determined by Pathology, were correlated to VLA-4 and CD38 expression. Short-term homing capacity of CLL cells was evaluated by adoptive transfer experiments. CLL cell viability and adhesion in stromal cell co-culture was determined. Results About 20% of CLL samples in our cohort displayed discordant VLA-4 and CD38 risk, with either high VLA-4 and low CD38 risk or vice versa. Using particularly such samples, we observed that VLA-4, and not CD38, was responsible for recirculation of CLL cells to murine BM. Human BM infiltration was also significantly higher in patients with high VLA-4 risk but not high CD38 risk. However, both molecules acted as independent prognostic markers. While both VLA-4 and CD38 expression were increased in BM-derived CLL cells, and VLA-4+ and CD38+ subpopulations showed enriched Ki-67 expression, VLA-4 did not contribute to CLL cell protection by stromal cells in vitro. Conclusions Our data argue for a prominent role of VLA-4 but not CD38 expression in the homing of CLL cells to BM niches and in human BM infiltration, but only a limited role in their protection by stromal cells.